Lightning location and mapping system using time difference of arrival (TDOA) technique - Abdul Malek, Zulkurnain (InTech, 2011)
Lightning strike is a dangerous natural phenomenon that can cause various problems. Telecommunication subscriber lines (TSLs) and electrical power lines are two systems that are almost always affected by nearby lightning strikes. Voltages in the telecommunication subscriber line (TSL) do get induced by nearby lightning strikes. The induced voltage can be carefully measured and lightning parameters such as the lightning current wave shape, lightning peak current and strike locations be reproduced. Better designs of lightning protection systems can be realised if data on lightning strike distribution in a given region is known. Commercial lightning mapping or locating systems are based on several technologies (Araujo, 2001; Kenneth, 2003). The two most popular methods are those based on the Time of Arrival (ToA) and the Directional Finder (DF) principles. An example of the lightning locating system (LLS) based on the ToA method is the country- wide LLS owned by the Malaysian national power company (TNB). The system is capable of determining the coordinates of the cloud-to-ground lightning strikes within 500m accuracy. However, for a localised distribution of lightning, say within 1 square km area, this accuracy is too large for the data to be meaningful.